1985
DOI: 10.1111/j.1365-2044.1985.tb10546.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the induction characteristics of thiopentone and propofol (2, 6‐di‐isopropyl phenol)

Abstract: SummaryA study has been undertaken to compare the induction characteristics of the new intravenous anaesthetic agent 2,6 di-isopropyl phenol, newly prepared in a lipid emulsion (propofol) with those of thiopentone. Despite a signijicantly higher incidence of pain on injection and spontaneous movement, the new agent "as felt to perform comparably to thiopentone as an induction agent. Unfortunately, propofol caused decreases in blood pressure which were signijicantly greater than those seen after thiopentone. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 7 publications
3
21
1
Order By: Relevance
“…5 The usual increase in blood pressure and HR following laryngoscopy and tracheal intubation was not observed in the two groups. Similar to previous reports, 18,19 more hypotension and bradycardia followed induction of anesthesia and tracheal intubation in the propofol group than in the thiopental group. The cardiovascular depressant effects of propofol may be attributed to direct myocardial depression and decreased systemic vascular resistance.…”
Section: Me Et Th Ho Od Ds Ssupporting
confidence: 91%
“…5 The usual increase in blood pressure and HR following laryngoscopy and tracheal intubation was not observed in the two groups. Similar to previous reports, 18,19 more hypotension and bradycardia followed induction of anesthesia and tracheal intubation in the propofol group than in the thiopental group. The cardiovascular depressant effects of propofol may be attributed to direct myocardial depression and decreased systemic vascular resistance.…”
Section: Me Et Th Ho Od Ds Ssupporting
confidence: 91%
“…Several reports of patients undergoing temporal lobe surgery for epilepsy show no seizure activity with propofol-induced anesthesia (20,21). Some authors have argued that propofol SLP are exaggerated spontaneous and involuntary movements as seen with other anesthetic agents such as methohexitone and ketamine (22,23). Several-researchers have suggested that in addition to propofol's GABA-mediated effects, it also demonstrates low-level glycine antagonism that could be responsible for observations of opisthotonous and myclonus.…”
Section: Discussionmentioning
confidence: 96%
“…Patients with hypovolemia, cardiac failure and hypertension are occasionally prone to greater decreases in arterial pressure with propofol. Propofol also causes lowering of the heart rate secondary to vagotonic effects [10][11][12]. These hemodynamic effects have been corroborated by observed significant decreases in HR, systolic, diastolic and MAP when propofol 2mg/kg was used.…”
Section: Resultsmentioning
confidence: 62%